Cat scratch disease requiring incision and drainage: A case report - Emile Jeunesse; Natalie Miller; Lisa Carroll; Mary Arbuthnot (Elsevier, 2024)
Introduction: Cat Scratch Disease (CSD) is a relatively novel disease that often resolves on its own or with antibiotic therapy and rarely requires surgical intervention. We present a case of CSD with a variable presentation that required surgical incision and drainage for resolution. Case presentation: This is a case of a 13-year-old African American male who presented with a 5cm × 8cm right-sided neck mass, with positive IgM titers for Bartonella henselae and parainfluenza virus following reported cat scratches. He was treated with a partial course of clindamycin before the diagnosis of CSD was made, then completed a five-day course of azithromycin. After three weeks with no resolution of systemic symptoms or reduction in mass size or pain, there was concern for malignancy. The mass was ultimately determined to be an enlarged lymph node and abscess via computed tomography and biopsy. It was surgically incised and drained, and a second five-day course of azithromycin was completed to prevent fistula formation. The surgery effectively treated the antibiotic resistant CSD, and resolution of systemic symptoms followed rapidly. Conclusion: This case report highlights a variable presentation of antibiotic resistant CSD, and that biopsy may be indicated in lymphadenopathy to rule out malignancy. Surgery for CSD is rare, but incision and drainage may be required for abscess formation with CSD, especially with concern for mass effect, and we recommend early surgical referral for these situations regardless of diagnosis.